(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes the manifestation of nationality in mimetic texts, which are an important component of nonverbal communication, based on semiotic and pragmatic approaches. The national-cultural characteristics of the mimetic sign system, their communicative function, and the role of national mentality in the interpretation process are scientifically substantiated.